On a Cell Entropy Inequality of the Relaxing Schemes for Scalar Conservation Laws (Journal of Computational Mathematics, 2000)
In this paper we study a cell entropy inequality for a class of the local relaxation approximation — The Relaxing Schemes for scalar conservation laws presented by Jin and Xin in [1], which implies convergence for the one-dimensional scalar case.
Keywords: Hyperbolic conservation laws; the relaxing schemes; cell entropy inequality.